Oracle-Guided Component-Based Program Synthesis - Jha, Susmit; Gulwani, Sumit; Seshia, Sanjit A.; Tiwari, Ashish (ICSE '10, May 2-8 2010, Cape Town, South Africa, 2010)
We present a novel approach to automatic synthesis of loopfree programs. The approach is based on a combination of oracle-guided learning from examples, and constraint-based synthesis from components using satisfiability modulo theories (SMT) solvers. Our approach is suitable for many applications, including as an aid to program understanding tasks such as deobfuscating malware. We demonstrate the efficiency and effectiveness of our approach by synthesizing bitmanipulating programs and by deobfuscating programs.